Analysing user-reported data for enhancement of SmokefreeTXT: a national text message smoking cessation intervention. Issue 6 (15th November 2016) - Cole-Lewis, Heather; Augustson, Erik; Sanders, Amy; Schwarz, Mary; Geng, Yisong; Coa, Kisha; Hunt, Yvonne
Abstract : Objective: This observational study highlights key insights related to participant engagement and cessation among adults who voluntarily subscribed to the nationwide US-based SmokefreeTXT program, a 42-day mobile phone text message smoking cessation program. Methods: Point prevalence abstinence rates were calculated for subscribers who initiated treatment in the program (n=18 080). The primary outcomes for this study were treatment completion and point prevalence abstinence rate at the end of the 42-day treatment. Secondary outcomes were point prevalence abstinence rates at 7 days postquit, 3 months post-treatment and 6 months post-treatment, as well as response rates to point prevalence abstinence assessments. Results: Over half the sample completed the 42-day treatment (n=9686). The end-of-treatment point prevalence abstinence for subscribers who initiated treatment was 7.2%. Among those who completed the entire 42 days of treatment, the end-of-treatment point prevalence abstinence was 12.9%. For subscribers who completed treatment, point prevalence abstinence results varied: 7 days postquit (23.7%), 3 months post-treatment (7.3%) and 6 months post-treatment (3.7%). Response rates for abstinence assessment messages ranged from 4.36% to 34.48%. Conclusions: Findings from this study illuminate the need to more deeply understand reasons for subscriber non-response and opt out and, in turn, improve program engagement and our ability to increase the likelihood for participants to stop smoking and measure long-term outcomes. Patterns of opt out for the program mirror the relapse curve generally observed for smoking cessation, thus highlighting time points at which to increase efforts to retain participants and provide additional support or incentives.